Front Cover: Rational Design of Isolated Tetrahedrally Coordinated Ti(IV) Sites in Zeolite Frameworks for Methyl Oleate Epoxidation (Chem. Asian J. 20/2024) - Sorasak Klinyod; Krissanapat Yomthong; Ploychanok Iadrat; Pinit Kidkhunthod; Kittisak Choojun; Tawan Sooknoi; Chularat Wattanakit (Chemistry - An Asian Journal, 2024)
Isolated Ti(IV)-zeolites have been rationally designed. The different aluminium topological densities of various zeolite frameworks lead to the creation of different degrees of vacant sites for hosting Ti(IV) active sites. The more vacancies in the host zeolite structure, the more isolated tetrahedrally coordinated Ti(IV) can be increased, especially in the BEA framework, eventually enhancing the catalytic performance in methyl oleate epoxidation towards methyl-9,10-epoxystearate. More details can be found in article number e202400669 by Chularat Wattanakit, and co-workers.
Keywords: Polyoxometalates: Synthesis and Applications; Chemical Synthesis and Reactions; Metal-Organic Frameworks: Synthesis and Applications